Enhancing Cracking Resistance and Post-Harvest Quality of Sweet Cherries (Prunus avium L.) Through Calcium and Potassium-Based Foliar Treatments - Alice Varaldo; Giovanna Giacalone (Horticulturae)
Sweet cherry (Prunus avium L.) is a highly valued fruit crop in Italy, but its production is challenged by environmental stresses, particularly rain-induced cracking, which significantly affects yield and quality. The aim of this study was to evaluate the effectiveness of foliar applications of calcium and potassium salts in reducing cracking and enhancing the overall quality and shelf-life of the sweet cherry cultivar “Regina”. The experiment was conducted in a commercial orchard in Piedmont, Italy, where the foliar application was studied across various parameters, including shoot growth, fruit yield, cracking incidence, and post-harvest quality during a 14-day storage period at 2 °C and 75% RH. Results showed that foliar treatments improved vegetative growth and increased the proportion of marketable fruit within the desirable Ø 28 mm size category. Moreover, treated fruits exhibited reduced cracking, reduced weight loss, and higher firmness during storage. Antioxidant activity and anthocyanin content were also better preserved in treated cherries since the day of the harvest. These findings indicate that foliar applications of macro- and micro-nutrients can mitigate cracking and improve the post-harvest performance of sweet cherries, providing a practical strategy to increase both yield and fruit quality in regions with adverse weather conditions.